Shaping Tension Structures with Actively Bent Linear Elements. Issue 3 (September 2013) - Van Mele, Tom; De Laet, Lars; Veenendaal, Diederik; Mollaert, Marijke; Block, Philippe
To achieve sufficient anticlastic (negative) curvature, membrane structures are tensioned between high and low anchor points, attached to the ground, buildings or poles. By integrating flexible bending elements in the membrane surface, an internal support and shape-defining system is created that provides more freedom in design and allows reducing the amount of external supports compared to traditional membrane structures. This paper presents a computational framework for form finding of tension structures with integrated, elastically bent, linear elements, based on three-dimensional bending moment vectors and a mixed force density formulation. With an implementation of this framework in CAD modelling software, users can control form and forces by prescribing any combination of force densities, forces, stiffness or lengths to the spline and cable-net elements. Sparse matrix operations are used to compute the resulting equilibrium shapes. The shape-defining possibilities of integrating 'bending-active' elements in tension structures are demonstrated through a series of design studies with various boundary conditions and spline configurations. The presented framework and implementation provide a straightforward method for the design of this hybrid structural system, and, therefore, facilitate its further exploration.